Teaching Reading Comprehension Through Question Answer Relationship Strategy To The Second Semester Students of Midwifery College of Andi Makkasau Parepare - Rasda Rahim (Universitas Sulawesi Barat, 2020)
RASDA RAHIM, 2018. Teaching Reading Comprehension Through Question Answer Relationship Strategy To The Second Semester Students of Midwifery College ofAndiMakkasauParepare.(Supervised by BasoJabu and Rafi’ahNur). The purpose of this research was to investigate whether or not the reading ability of the second semester students of Midwifery College of Andi Makkasau Parepare can be improved through Question Answer Relationship strategy. This research used a quasi-experimental. The subject of this research was the second-semester students of Midwifery College of Andi Makkasau Parepare. There were two classes, class B as an experimental group treated through QAR reading strategy and class A as a control group treated through 321 reading strategy. It utilized total sampling technique. The participant of each group was 40 students. The instrument used in this research was a multiple-choice reading test. The data obtained through the test were analyzed quantitatively by using t-test formula. The research reveals that there is a significant difference between students’ reading comprehension after being taught through QAR reading strategy. It is proved by the data analysis. It is shows that the mean score of posttest is higher than the mean score of pretest (76 > 53). Besides the mean score, there was also the result of t-test to examine the research hypothesis. Based on the result data analysis, the t-score value higher than the t-table (5.371701>1,668). It is indicates that there is significance improvement of students’ reading comprehension literally, inferentially and critically after the treatment. It proves the research hypothesis that the reading comprehension ability of the second semester students of the Midwifery College of Andi Makkasau Parepare can be improved significantly through QAR reading strategy.